Asymmetric Synthesis of Ethers by Catalytic Alkene Hydroalkoxylation - Xie, Wen-Bin; Li, Zhi (Synthesis, 2020)
Many chiral ethers have important physiological activities. Although many asymmetric hydroalkoxylations of olefins with alcohols or phenols have been developed to make chiral ethers, challenges still remain in achieving high reactivity and selectivity over an ever-increasing diversity of alkenes and alcohols. In this review, recent developments on catalytic asymmetric alkene hydroalkoxylations are summarized based on the substitution patterns of alkenes.1 Introduction2 Asymmetric Hydroalkoxylation of Non-Activated Alkenes2.1 Intramolecular Additions2.2 Intermolecular Additions3 Asymmetric Hydroalkoxylation of Enol Ethers3.1 Intramolecular Additions3.2 Intermolecular Additions4 Asymmetric Hydroalkoxylation of α,β-Unsaturated Carbonyl Compounds4.1 α,β-Unsaturated Ketones and Aldehydes as Substrates4.2 α,β-Unsaturated Esters, Amides and Carboxylic Acids as Substrates5 Asymmetric Hydroalkoxylation of Allenes5.1 Intramolecular Additions5.2 Intermolecular Additions6 Conclusion
Keywords: hydroalkoxylation; asymmetric catalysis; oxa-Michael addition; enantioselective addition; alkenes; allenes; chiral ethers